PERBEDAAN HASIL PEMERIKSAAN LEUKOSIT URINE MENGGUNAKAN URINE ANALYZER DENGAN SEDIMEN URINE - Lydia Erdi Putri; Anak Agung Ayu Eka Cahyani; Putu Ayu Parwati (PT. GIAT KONSELING NUSANTARA, 2026)
Urinalysis is a routine urine examination in the laboratory that includes macroscopic, chemical, and microscopic (urine sediment) analysis. One of the most commonly found elements in urine sediment is leukocytes. Until now, the gold standard for urine sediment examination has been manual microscopy. However, with technological advancements, many laboratory personnel now use automated methods such as the Cybow Reader, which allows for quicker analysis.The aim of this study is to determine the difference in urine leukocyte results between the Cybow Reader and the manual microscopic (sediment) method. This research is experimental in nature. The population of the study consisted of all patients undergoing urinalysis at Seger Waras Hospital in May 2025. Using accidental sampling, a total of 20 samples were collected. The urinary leukocyte count obtained using the urine analyzer method showed results of 25/ul in 17 samples (85%), 100/ul in 1 sample (5%), and 500/ul in 2 sampels (10%). Meanwhile, the urinary leukocyte count using the urine sediment method showed results of +1 in 17 samples (85%),+2 in 1 sample (5%) and +3 in 2 samples (10%).The data were analyzed using the Shapiro-Wilk normality test, followed by the Kruskal-Wallis test. The Kruskal-Wallis test yielded a p-value of 0.00, indicating that there is a significant difference in urine leukocyte results between the urine analyzer and the sediment method.